An ethnomathematical study of Tchadji: about a Mancala type boardgame played in Mozambique and possibilities for its use in mathematics education - Ismael, Abdulcarim (My University, 2004)
This research is in the field of ethnomathematics. The study was carried out in three phases with the Tchadji-game being its principal focus. Tchadji is a traditional game played at Ilha de MOyambique, a small Island situated on the northeast coast of Mozambique. Tchadji belongs to a class of board games known as Mancala, which are thousands of years old and are played throughout the African continent as well as in other parts of the world. Mancala games have only recently received due attention as a topic for research. The first phase of the research was carried out in the school mathematics classroom. The outcomes of this phase indicated that games like Tchadji and the three stones (a variant of the Muravarava game) as a part of Mozambican culture are also rich in providing opportunities for activities in the mathematics classroom related to the development of key probabilistic concepts. Quasi-experimental research involving the researcher, 4 mathematics teachers and 162 students showed statistically significant positive effects on attitude towards the learning of, and performance in probability. These outcomes were corroborated by qualitative research. The second phase of this study consisted of ethnographic research amongst master Tchadji players, which explored the mathematical ideas embedded in the Tchadji-game and in the procedures for playing the game. The results of this phase of the research revealed that, the Tchadji-players had mathematical knowledge, skills and ways of thinking such as counting, logical thinking, calculation, visualisation, recognition of different numerical patterns and infinity. These results are described in terms of examples taken from different critical moments of the recorded matches of Tchadji. This way of iii Abstract (PhD thesis) presenting the results gives insight into the complexity of the methodology used. It also uncovers different aspects of playing Tchadji, like rules, strategies and tactics. A need for further investigations of this nature for uncovering mathematical ideas in traditional culture is also indicated by this research. As advocated in ethnomathematical research an intervention with (pre and in-service) student teachers formed the third phase of the research. The results of this phase indicated that the 24 teachers, who participated in the research, showed enthusiasm, satisfaction and excitement in experiencing the mathematical richness of Tchadji and in appreciating possibilities for the use of Tchadji in the mathematics classroom. They were able to analyse the game independently and to identify embedded mathematical ideas in the game, like logical thinking, counting and empirical and mental calculation. The research makes contributions to the field of ethnomathematics itself, to ethnographic research methodology and to the pedagogy of mathematics.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Science, 2004
Keywords: Ethnomathematics; Mathematics -- Study and teaching